HUBUNGAN MOTIVASI DIRI DAN DUKUNGAN TENAGA KESEHATAN DENGAN KEPATUHAN DIET PENDERITA DM TIPE 2 DI WILAYAH KERJA UPTD PUSKESMAS BANGKINANG KOTA TAHUN 2019 - ERMA KASUMAYANTI; BONITA RAHAYU (Universitas Pahlawan Tuanku Tambusai, 2019)
Diabetes mellitus (DM) is one of the biggest global health emergencies in the 21st century. Diabetes mellitus is a genetic or hereditary disease that is difficult to cure but can be controlled with a 3 J diet program that is the number, type and schedule. Patient adherence to the diet program is one of the obstacles in patients with type 2 diabetes mellitus. Compliance is caused by many factors, one of which is self-motivation and support of health workers. The purpose of this study was to determine whether there is a relationship between self-motivation and support of health workers with diet compliance with DM type 2 sufferers in the Work Area of the Community Health Center of Bangkinang City. This research is a quantitative study with cross sectional design. The sample in this study were some patients with type 2 diabetes mellitus in the work area of the City Health Center Bangkinang, amounting to 86 people with a purposive sampling technique. Data processing using chi-square test. The results showed that there was a significant relationship between self-motivation (p value = 0,000) and support of health workers (p value = 0.020) with diet compliance of DM type 2 sufferers in the Bangkinang City Health Center Work Area. The results of this study are expected to be used by people with type 2 diabetes are expected to be able to comply with the correct diet according to diet 3j, namely the type, amount and schedule recommended by health workers, patients are expected to carry out healthy living behaviors.